A-270 Synergistic Relationship of Prenatal Hurricane Sandy Exposure and Postnatal Suicidal Ideation on Child Fear During the COVID-19 Pandemic. (17th August 2022) - Sie, Sheow Yun; Maharaj, Reena; Lopez, Johnny; DeIngeniis, Donato; Monir, Faria; Nomura, Yoko
Abstract: Objective: In-utero stress, maternal suicidal ideation, and COVID-19 lockdown have the potential to effect mothers and eventually their offspring. However, research on the effects of these factors on child fear has insubstantial results. Current study explored the effects of the interaction between in-utero environmental stress related to Superstorm Sandy and postnatal suicidal ideation on child fear level during the COVID-19 pandemic. 115 mother and their children, ages 5 to 10 were recruited for the study (M = 8.62). Participants completed Edinburgh Postnatal Depression Scale (EPDS) and COVID-19 related Child Fear Questionnaires. The EPDS was used to screen for maternal depressive disorders, includes a question on suicidal ideation. A two-by-two Factorial ANOVA was conducted to compare the main effects of in-utero hurricane Sandy exposure and postnatal suicidal ideation, and the interaction of the two on child fear during COVID-19 pandemic. Results showed a significant interaction of mothers' prenatal hurricane exposure and postnatal suicidal ideation towards child fear during the pandemic, F (1, 111) = 3.77, p = .05. It also showed an elevated increase in child fear during pandemic among children with mothers that were exposed to Hurricane Sandy during pregnancy and presented postnatal suicidal ideation. These results highlighted the important of preventive strategies to mitigate postnatal distress and support families in the post-COVID-19 context.